2006
DOI: 10.1590/s0101-20612006000400024
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients in the cassava (Manihot esculenta Crantz) leaf meal at three ages of the plant

Abstract: SUMMARYThe high number of cassava cultivars adapted to many different regions provides a wide variation in the chemical composition of cassava leaves meal (CLM). Therefore, the contents of some nutrients in CLM from five cultivars at three ages of the plant were investigated in order to select the cultivars and ages with superior levels of these nutrients. When the plants were 12 months old, the highest levels of crude protein (CP), β-carotene, iron, magnesium, phosphorus and sulfur were observed. The IAC 289-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
3
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 15 publications
7
38
3
6
Order By: Relevance
“…The lipid (13.9%) and ash (5.96%) contents observed in cassava leaf flour were similar to those observed in previous studies, in which lipid contents ranged from 3.30 to 16.0% and ash content ranged from 4.62 to 8.30% (ORTEGA-FLORES et al, 2003, WOBETO et al, 2006.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The lipid (13.9%) and ash (5.96%) contents observed in cassava leaf flour were similar to those observed in previous studies, in which lipid contents ranged from 3.30 to 16.0% and ash content ranged from 4.62 to 8.30% (ORTEGA-FLORES et al, 2003, WOBETO et al, 2006.…”
Section: Resultssupporting
confidence: 89%
“…These results have also been observed in previous studies, which showed protein contents ranging from 20.77 to 37.94% (ORTEGA-FLORES et al, 2003;CORRÊA, 2004;WOBETO et al, 2006).…”
Section: Resultssupporting
confidence: 88%
“…Modesti (2006) WOBETO et al (2006). Estas variações, além da interferência da cultivar, época de colheita, podem ser devidas também as diferentes metodologias utilizadas para a determinação desse componente.…”
Section: Resultado E Discussãounclassified
“…Os teores elevados de proteínas nas folhas de mandioca têm sido observados em vários trabalhos, entre 20,77 a 37,94 g/100g de matéria seca (ORTEGA-FLORES et al, 2003;WOBETO et al, 2006;CORRÊA et al, 2004;MELO, 2005). Esses teores de proteínas pode ser comparado ao de hortaliças convencionais, como a couve (30,84 g/100g massa seca) (FONSECA et al, 2002).…”
Section: Introductionunclassified
“…Evaluating five cassava cultivars and three harvesting times, Wobeto et al (2006) found sulfur values between 2.8 and 4.1 g/kg DM, whereas phosphorus varied between 2.4 and 3.3 g/kg DM. Potassium values varied between 11.2 and 16.3 g/kg DM, corroborating the information obtained in this experiment.…”
Section: Resultsmentioning
confidence: 98%